Cyanoacrylate Glue Burn Injury in 2 Years Old Child - Wardhana, Aditya; Christabella, Rininta (Jurnal Plastik Rekonstruksi, 2023)
Cyanoacrylate, a compound formed from formaldehyde and alkyl cyanoacetate, serves as a potent adhesive in daily life, cosmetics, medicine, and industry. Variants like methyl 2-cyanoacrylate and ethyl 2-cyanoacrylate are common for daily  and industrial use, with butyl 2-cyanoacrylate preferred in surgery as an adhesive for its low toxicity. While typically safe for skin, frequent contact can lead to dermatitis, paronychia, and onycholysis. This case report highlights a superficial burn in a two-year-old child caused by cyanoacrylate adhesive. Such burns are rare but require attention. Treatment involves gently separating the adhesive from the skin using soapy water, followed by the use of acetone, petroleum jelly, 0.9% NaCl solution, or 5% sodium bicarbonate solution, followed by the use of pumice stone or nail file to remove residue. Preventive measures include careful glue placement to limit access, especially by children. Caution is crucial when handling cyanoacrylate adhesive near cotton or wool due to its adhesive properties. In summary, cyanoacrylate offers versatility but requires caution to prevent dermatological issues and burns, especially when catalysed by cotton.